Prognostic factors of pain syndrome after uterine artery embolization in women with uterine leiomyoma - S A Sosin; V V Privorotskiy; I E Zazerskaya; V N Kustarov (IP Berlin A.V., 2017)
The pain syndrome after uterine artery embolization can vary from slight to very pronounced. Therefore, choosing an adequate method of anesthesia is extremely important in this method of treatment. Aim of the study: pre-operative prognosis of the severity of the pain syndrome and selection of the optimal managing tactics in postoperative period. Materials and methods. Our study includes 65 patients, the patients are divided into 2 groups depending on the method of anesthesia. For analgesia in the perioperative period, the patients of the first group underwent anesthesia by the method of epidural anesthesia (n=44). In the second group (n=21), the operation was performed under local anesthesia. Results. In group 1, the intensity of the pain syndrome was 5.38 on the 1st day, and 2.36 on the 4th day of the postoperative period. In this case, a clear relationship between fibroid size and the severity of the pain syndrome was revealed. In the second group of patients (n=21) on the 1st day of the postoperative period, the average value of the intensity of the pain syndrome was 7.72. On the 4th day of the postoperative period, the average value of the pain syndrome was 4.95. When analyzing the intensity of the pain syndrome, depending on the size of fibroids, a direct correlation was also found in the patients of this group. Conclusion. Pain syndrome depends primarily on the size of the fibroids. Epidural anesthesia can be considered to be the most effective method of anesthesia. The use of epidural anesthesia is especially justified in the presence of large-sized fibroids (>8 cm). It is advisable to discharge patients not earlier than 4 days after the operation, when a reliable control of the intensity of the pain syndrome is achieved.